Investigation on Structural, Surface Morphological and Dielectric Properties of Zn-doped SnO2 Nanoparticles - Sagadevan,Suresh (2016)
Zinc doped Tin oxide (SnO2) nanoparticles were prepared by co-precipitation method. The average crystallite size of pure and Zn-doped SnO2 nanoparticles was calculated from the X-ray diffraction (XRD) pattern. The FT-IR spectrum indicated the strong presence of SnO2 nanoparticles. The morphology and the particle size were studied using the scanning electron microscope (SEM) and transmission electron microscope (TEM). The particle size of the Zn-doped SnO2nanoparticles was also analyzed, using the Dynamic Light Scattering (DLS) experiment. The optical properties were studied by the UV–Visible absorption spectrum. The dielectric properties of Zn-doped SnO2 nanoparticles were studied at different frequencies and temperatures. The ac conductivity of Zn-doped SnO2 nanoparticles was also studied.